Traditional Malay keris pandai saras design in Malaysia - Norman, Nurulliyana (2017)
Keris Pandai Saras is one of the traditional Malay weapons heritages. In Malaysia, there are various types of keris namely Keris Pandai Saras, Keris Melela, Keris Alang and others. Detail visual documentation about keris in Malaysia required visual description about features of traditional design elements, which significantly represent the character of the Keris Pandai Saras. Therefore, this research only focuses on Keris Pandai Saras and the objectives of this research was to identify the type of traditional design that is embedded in the Keris Pandai Saras, and to identify the functions of umbi design in Keris Pandai Saras blade which include the design of hilt and the sheath of the keris. The design of keris is obtain from the data collection through interviews and observations. The sample is grouped according to the segment of keris, which were blade, hilt and sheath and supported with visual digital images. The findings describes that Keris Pandai Saras is recognized from the four main segments of the keris such as blade, which is called as ganja or aring (end upper part), the kerawang or akut (carrying goods), and strong iron. The sheath features was Sampir Tebar Layar and for the hilt was hilt Anak Ayam. This research findings, were parallel with design of Keris Pandai Saras which has been said to be used by the Sultan in Malaysia can be documented for future references, re-introduce this precious treasure to the societies will regain our inheritance of the Malay race and consequently will keep this country heirloom treasures in its place for the keris.